2014
DOI: 10.5455/cap.20140116011913
|View full text |Cite
|
Sign up to set email alerts
|

Sigara Bagimliliginin Genetigi

Abstract: ÖzetSigara birçok hastalığın sebepleri arasındadır ve her yıl 5 milyon insanın ölümüne neden olarak, en önemli ölüm nedenleri arasında yer almaktadır. Bağımlılık, sigara kullanımının yol açtığı en önemli sendromlardandır ve içerdiği nikotin ile ilişkilendirilmiştir. Sigara bağımlılığının nedenleri farklı bileşenleri ile yoğun bir şekilde araştırılmıştır. Epidemiyolojik, farmakolojik, nörobiyolojik ve genetik çalışmalar başlıca çalışma alanlarıdır. Sigara ve nikotin bağımlılığının genetiği 50 yıldır çalışılmak-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
0
0
Order By: Relevance
“…Studies have shown that environmental factors play a significant role in starting smoking, and genetic factors play a significant role in the transition from regular smoking to addiction. [5] Dopamine (DA) was defined by Arvid Carlsson about 60 years ago. [6] While the DA subtypes of D1 and D2 were known until 1988, studies have defined the D3 and D4 receptors as "D2-like" and the D5 receptor as "D1-like" according to their pharmacological and primary mechanisms of action.…”
mentioning
confidence: 99%
“…Studies have shown that environmental factors play a significant role in starting smoking, and genetic factors play a significant role in the transition from regular smoking to addiction. [5] Dopamine (DA) was defined by Arvid Carlsson about 60 years ago. [6] While the DA subtypes of D1 and D2 were known until 1988, studies have defined the D3 and D4 receptors as "D2-like" and the D5 receptor as "D1-like" according to their pharmacological and primary mechanisms of action.…”
mentioning
confidence: 99%